PERAN LAHAN SAWAH TADAH HUJANTERHADAP KETAHANAN PANGAN NASIONAL DI KABUPATEN DELI SERDANG, SUMATERA UTARA - Jonharnas Haryani Jonharnas; Sri Haryani Sitindaon (Jurnal Agroteknologi, 2017)
Deli Serdang District is one of regencies in North Sumatra which has rainfed and most extensive that is 19,365 ha. The study was conducted to determine the development of rice farming in the rainfed areas (Farming Index, productivity and analysis of farming) paddy rice fed land rainfed. The study was conducted from January to June 2016. The study is a descriptive exploratory study with sampling by purposive sampling in the village which has the most extensive rainfed the village Durian, Sub District Pantai Labu and village Serdang, Subdistrict Beringin, Deli Serdang District, North Sumatra Province. The collection of data and information is done by direct observation and indept interview. Land rainfed in Deli Serdang District average index of plants 2 times a year lower (10,292 ha) compared with irrigated land (20,950 Ha). Although the rainfed areas, farmers in Deli Serdang managed to plant two times a year with mechanized pumps to irrigate paddy fields during the dry season. Production rice at dry season with mechanized irrigation pump is higher (6.25 t/ha) than in the dry season without irrigation, mechanization pump (3.20 t/ha and the rainy season (4.50 t/ha). The results of the economic analysis is obtained that the B/C Ratio rice farming in rainfed areas during the rainy season was higher (1.60) compared to the dry season with mechanized irrigation pump (1.50) and dry season without irrigation (1.001). This happens because the amount of input issued to conduct mechanized irrigation pumps during the dry season.